Generation of Gellan Gum-Based Adipose-Like Microtissues - Lago, Manuela Ermelinda Lopes (2018)
Adipose tissue is involved in many physiological processes. Therefore, the need for adipose tissue-like analogues either for soft tissue reconstruction or as in vitro testing platforms is undeniable. In this work, we explored the natural features of gellan gum (GG) to recreate injectable stable adipose-like microtissues. GG hydrogel particles with different percentages of polymer (0.5%, 0.75%, 1.25%) were developed and the effect of obtained mechanical properties over the ability of hASCs to differentiate towards the adipogenic lineage was evaluated based on the expression of the early (PPARγ) and late (FABP4) adipogenic markers, and on lipids formation and accumulation. Constructs were cultured in adipogenic induction medium up to 21 days or for six days in induction plus nine days in maintenance media. Overall, no significant differences were observed in terms of hASCs adipogenic differentiation within the range of Young’s moduli between 2.7 and 12.9 kPa. The long-term (up to six weeks) stability of the developed constructs supported its application in soft tissue reconstruction. Moreover, their ability to function as adipose-like microtissue models for drug screening was demonstrated by confirming its sensitivity to TNFα and ROCK inhibitor, respectively involved in the repression and induction of the adipogenic differentiation.